Comparison of botulinum neurotoxin type A formulations in Asia - Frevert J; Ahn KY; Park MY; Sunga O (Dove Medical Press, 2018)
Jürgen Frevert,1 Ki Young Ahn,2 Mee Young Park,3 Owen Sunga4 1Merz Pharmaceuticals GmbH, Frankfurt, Germany; 2Dr. Ahn’s Plastic and Aesthetic Surgical Clinic, Daegu, South Korea; 3Department of Neurology, Yeungnam University School of Medicine, Daegu, South Korea; 4Merz Asia Pacific, Singapore Introduction: All protein-based therapeutics, such as botulinum neurotoxin type A (BoNT/A), are potentially immunogenic and can lead to anaphylaxis, autoimmunity, or diminished or complete absence of therapeutic efficacy, especially if administered repeatedly. Therefore, the protein quantity in BoNT/A products is an important consideration when selecting products for treatment. However, essential formulation data are not always publicly accessible. Materials and methods: The neurotoxin protein content of products newly introduced in Asia, such as (listed alphabetically) Botulax®, Meditoxin®, Nabota®, and Relatox®, was measured by sandwich enzyme-linked immunosorbent assay with antisera directed against BoNT/A compared to Xeomin®. Results: Compared to Xeomin with no inactive neurotoxin, although Botulax and Nabota contained 844 and 754 pg of neurotoxin protein, respectively, the percentage of inactive neurotoxin was calculated to be 103 and 81, respectively, while the potency per pg of neurotoxin was 0.118 and 0.133 U, respectively. Meditoxin and Relatox had 575 and 578 pg of neurotoxins, respectively, marginally higher than that of Xeomin, while the percentage of inactive neurotoxins was 38 and 33, respectively, and the potency per pg of neurotoxin was 0.174 and 0.173 U, respectively. However, Xeomin, which has 416 pg/vial of purified neurotoxin and 0.240 U of efficacy per pg of neurotoxin, has the lowest neurotoxin protein content and consequently the highest specific potency compared to the four Asian BoNT/A preparations in this study. Conclusion: Although Botulax and Nabota had more neurotoxin than Xeomin in an equivalent volume, they contained greater amounts of inactive neurotoxin. In addition, although Meditoxin and Relatox had slightly more neurotoxin than Xeomin, both contained greater amounts of inactive neurotoxin. Keywords: botulinum neurotoxin type A, purity, potency, immunogenicity, Asia